Postharvest handling and marketing of tomato in Leon, Iloilo - Neturada, Felicitas Montalban (University of the Philippines in the Visayas, 2005)
Tomato is one of the most important vegetable crops and a major imported vegetable in fresh or chilled form in the Philippines. In Western Visayas, Iloilo is the largest tomato producer supplying 91.7% of the region's production. In Iloilo, eon is dubbed as the "vegetable basket" of the Province and the largest producer of tomato not only in Iloilo but also in the entire Western Visayas. Using purposive sampling, 31 tomato farmers from an estimated population of 65 tomato growers from the eight baangay sites were selected as respondents of the study recommended by the OMA of Leon for their high production level. Collection of the primary data from the respondents was through survey employing [personal interview. They preferred on-season planting unmindful of using unidentified variety of tomato. After harvesting, majority of respondents sold their tomatoes in the bagsakan center of Leon on wholesale basis. Supply and demand were the basis of pricing and trading ensues with both the farmer and buyer negotiating on the right price. Hired tricycle was mostly the means of transporting the produce from the farm to the trading point in spite of the respondents' awareness of compression damage caused by the kind of transport used, which lower the quality and marketability of their products. Low buying price and lack of buyers or no market at all were the problems of the respondents in marketing their produce. To improve the tomato industry in Leon, Iloilo, the farmer-respondents recommended for the establishment of a processing plant to transform tomatoes into more durable forms like tomato paste, catsup, sauce, puree, candies, etc., especially during overproduction. They also recommended for a cold storage to prolong the shelf life of their produce. They badly need the assistance of the DA-RFU 6 with its Agribusiness and Marketing Assistance Division (AMAD) on market linkaging and networking. Another promising area to explore on tomato productio in Leon is hte adoption of organic farming technology for a more competitive and quality product.